Implementación de Sistema de Registro de Dosimetría Radiológica en pacientes del Instituto Nacional de Cancerología (INCan). - Tapia Acosta, José Juan; Castillo López, Jorge Patricio; Rocha Nava, Sandra Luz; Galván Espinoza, Héctor Alejandro (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Imaging studies with ionizing radiation are carried out at the Mexico’s National Cancer Institute, which may represent risks to the health of the patient, which is why there is a need to monitor the effective dose given to patients. This document describes the implementation of a computer system that allows extraction of patient and study data, calculation of effective dose and reference values that allow quality control of the amount of ionizing radiation used in imaging studies.